Digest: On the origin of a possible hybrid species. (1st November 2022) - Stankowski, Sean
Abstract: Hybrid speciation—the origin of new species resulting from the hybridization of genetically divergent lineages—was once considered rare, but genomic data suggest that it may occur more often than once thought. In this study, Noguerales and Ortego found genomic evidence supporting the hybrid origin of a grasshopper that is able to exploit a broader range of host plants than either of its putative parents.